Catastrophe theory - Woodcock, A. E. R. (Penguin books, 1978)
Contents: 1978, First Edition. Hardcover with dust jacket. The black background, yellow image, with white and red lettering on the dust jacket. The dust jacket is fair to good condition. The book is in very good condition. Alexander Woodcock and Monte Davis, Authors. Corners are sharp and clean. Edges/corners/spine show light wear and rubbing on the jacket. The endpages are red. Grey boards with black trim to the spine with silver lettering. The old sales price is on the inside dust jacket flap is still there. Total 152 pages. Contains black and white drawings. Approximate size, 5.50 x 8.50. The pages are clean and without markings and tears. The spine is tight and straight. Printed in the USA. E. P. Dutton, New York, Publishers. "The revolutionary new way of understanding how things change." "The book serves to explain a fraction of the phenomena to which Thom has suggested its application, the theory's reach will be extraordinary, the development of the ego, the origin of life, evolution, death, and language, among other things.....James Gorman." "An intellectual revolution...Catastrophe theory affords novel and deep insights into the world in which we live...Ian stewart." "Catastrophe theory is one of many attempts that have been made to deduce the world by thought alone...an appealing dream for mathematicians, but a dream that cannot come true.....Zahler and Sussmann." An interesting read that you will want to take a real look at this one, excellent book for thought provoking. *11BC3